QSAR MODELING OF 2-[CH(OH)X]-5,8-(OY)2 -1,4-NAPHTHOQUININES AGAINST L1210 CELLS USING MULTIPLE LINEAR REGRESSION - Ajeet .; Brajpal Singh; Vipul Kumar (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Quinones are present in many drugs such as anthracyclines, daunorubicin, doxorubicin, mitomycin, mitoxantrones and saintopin, which are used clinically in the therapy of solid cancers. The cytotoxic effects of these quinone are mainly due to the inhibition of DNA topoisomerase-II. It is the necessity to develop the 1,4-Naphthoquinone analogues with Cytotoxic effect. Here 2-[CH(OH)X]-5,8-(OY)2-1,4-Naphthoquinines analogues have been used to correlate the cytotoxic activity with the Eccentric Connectivity index (ECI), Fragment Complexity (FC) and McGowan Volumes (MG) for studying the Quantitative Structure Activity Relationship (QSAR). Correlation may be an adequate predictive model which can help to provide guidance in designing and subsequently yielding greatly specific compounds that may have reduced side effects and improved pharmacological activities. We have used Multiple Linear Regression (MLR), one of the best methods for developing the QSAR model. Results from this QSAR study have suggested that ECI, FC and MG are the important descriptors for cytotoxic activities of 1,4-Naphthoquinones against L1210 cells. For the validation of the developed QSAR model, statistical analysis such as data point-descriptor ratio, fraction of variance, cross validation test, standard deviation, quality factor, Fischer’s test; and internal validation such as Y-randomization test have been performed and all the tests validated this QSAR model.Key words: 1,4-Naphthoquinones, QSAR, Eccentric connectivity index, Fragment complexity, McGowan Volume, Multiple Linear Regression